Legal review of land bank management of abandoned land in Indonesia under social function principles - Alya Meswati; Nabila Zatadini (Journal of Law Science, 2026)
Land is a resource that plays a crucial role in society, as it is closely related to economic, social, and national development aspects. However, in practice, many parcels of land that have been granted rights to individuals or legal entities are not utilized optimally, resulting in abandoned land. This study aims to analyze the nature of asset ownership by the Land Bank Agency within the Indonesian land law system, as well as the authority of the institution in managing state land. The research method used is normative legal research with statutory and conceptual approaches. The legal materials consist of primary, secondary, and tertiary sources collected through literature study and analyzed qualitatively. The results show that asset ownership by the Land Bank Agency cannot be interpreted as private ownership, as the land managed remains under state control. The Land Bank Agency functions as a managing institution with the authority to plan, control, manage, utilize, and distribute both state land and abandoned land. The existence of this institution is expected to optimize land utilization and realize agrarian justice based on the social function principle of land rights.